2014
DOI: 10.1016/j.joca.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 10-week toe-out gait modification intervention in people with medial knee osteoarthritis: a pilot, feasibility study

Abstract: These preliminary findings suggest that toe-out gait modification is feasible in people with medial compartment knee OA. Preliminary changes in clinical and biomechanical outcomes provide the impetus for conducting larger scale studies of gait modification in people with knee OA to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
109
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(124 citation statements)
references
References 40 publications
13
109
2
Order By: Relevance
“…However, the differences in the first peak knee adduction moment were not significant. A reduction in the second peak knee adduction moment has been associated with a reduced risk of OA progression, and there have been studies on gait retraining interventions to reduce the second peak knee adduction moment [7,27]. We also did not observe significant differences in medial cartilage or meniscus T 1q in any of the groups.…”
Section: Discussionmentioning
confidence: 43%
“…However, the differences in the first peak knee adduction moment were not significant. A reduction in the second peak knee adduction moment has been associated with a reduced risk of OA progression, and there have been studies on gait retraining interventions to reduce the second peak knee adduction moment [7,27]. We also did not observe significant differences in medial cartilage or meniscus T 1q in any of the groups.…”
Section: Discussionmentioning
confidence: 43%
“…reduction (e.g. 25-98% in [35] 0-45% in [25]). Future studies on gait modification may benefit by considering the motion of the whole body, even if a specific kinematic change is of primary interest.…”
Section: Discussionmentioning
confidence: 99%
“…To use a sports analogy, Usain Bolt is faster than the authors, and has a longer stride length, but taking longer steps would not necessarily increase our sprinting speeds. An impressive recent pilot study showed that a modified gait (toe-out) reduced the late-stance KAM and knee pain in a 10-week training study of individuals with medial knee OA [25]. Other similar studies on the long-term efficacy and mechanical consequences of gait modification are needed before it can be used confidently as an intervention.…”
Section: Stride (%) Grf Z (Bw)mentioning
confidence: 99%
“…Hunt et al [31] reported that participants with a 10-week toe-out gait modification intervention have minimal to moderate difficulty, and 33% of participants feel joint discomfort within the first 2 weeks. The authors reported no data regarding the negative side effects over the long-term.…”
Section: Discussionmentioning
confidence: 99%
“…For the knee flexion moment, the moment is associated with the medial knee compression force [33], few longitudinal and interventional studies have examined the influence on medial knee OA. The knee flexion moment during the toe-out gait is significantly higher than that during normal walking [6], and the toe-out gait is reported to have beneficial effects for patients with knee OA after a 10-week intervention [31]. Although the peak knee flexion moment has no clear influence on medial knee OA [31], a potentially negative effect of the Nanba gait is that the moment could be increased during the stance phase.…”
Section: Discussionmentioning
confidence: 99%